Redefining Collaborative Governance in the Digital Age: insights from an integrative systematic review on the role of ICT in collaboration - Viana, Luna Bouzada Flores (Technium Social Sciences Journal, 2025)
Governments increasingly face wicked and complex problems that demand innovative approaches and multisectoral collaboration. The “collaborative governance” concept emphasizes government-led coordination among public, private, and civil society actors to foster consensus and collective action. Simultaneously, Information and Communication Technology (ICT) has emerged as a transformative force in governance, facilitating leadership, trust-building, and stakeholder participation. ICT remains peripheral in foundational collaborative governance frameworks despite its potential, revealing a critical conceptual gap in understanding its role. This study addresses this gap through a systematic review of two decades of academic literature (2003–2023). It focuses on how ICT is framed, its functional roles, and the tools it offers to support governance processes. The findings highlight ICT’s capacity to reshape leadership dynamics, foster trust in distanced communication, and enhance participatory mechanisms. Recognizing the absence of a comprehensive framework, the study proposes adapting the “Integrative Framework for Collaborative Governance,” positioning ICT as an operational, non-human participant in joint capacity for action while trust and value-based decision-making remain human-centered. By bridging public administration and ICT scholarship, this research advocates for a paradigm shift that integrates ICT into collaborative strategies for addressing wicked problems. It underscores the necessity of sociotechnical approaches to governance and offers actionable insights for policymakers and practitioners navigating the complexities of an increasingly digital and interconnected world.